التوسع في إنتاج الغازات غير التقليدية: حل لأزمة الطاقة أم تفاقم للمشكلة البيئية - الغايش، عزمى محمد عبدالجليل; الغايش، علياء محمد عبدالجليل (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنات بدمنهور, 2020)
تعتبر الطاقة عنصرا رئيسيا في عملية التنمية الاقتصادية، ويؤدي العمل على خفض تكلفتها أو دعمها إلى التوسع في العملية الإنتاجية وازدهار النشاط الاقتصادي، ومع تقلبات أسعار مصادر الطاقة الاحفورية التي تواجه الدول المستوردة للطاقة كان هناك درس مهم يجب الاستفادة منه من وهو ضرورة تنويع مصادر الطاقة، والسعي نحو تحسين كفاءة الطاقة، والاستعداد لاستيعاب درجة عالية من تقلب أسعارها، والتقليل من احتمال حدوث صدمات في المستقبل، إضافة إلى الحاجة لاستمرار التنمية الاقتصادية بزيادة المعروض من الطاقة الذي يقابل الطلب عليها بوصفها المحرك للعملية الاقتصادية. وقد أثار التقدم المفاجئ في تقانة إنتاج الغاز غير التقليدي وخاصة في الولايات المتحدة اهتمام المهتمين بشئون الطاقة، حيث سمح ذلك التقدم التقني بتواصل اقتصادي أكبر مع إمدادات الغاز الطبيعي التقليدي خاصة مع تحقيق إنتاج واسع النطاق لتجمعات الغاز غير التقليدي. وعلى الرغم من ما تبشر به التطورات التكنولوجية لتلك الصناعة بترقي مكانه الغاز غير التقليدي، والتأثيرات الاقتصادية التي يمكن أن يحدثها خاصة مع تطور اكتشافات موارده مع مرور الزمن على منتجي ومستوردي الطاقة على حدا سواء. ألا أن الآراء انقسمت بين معارض ومساند لاستغلاله سواء لأثاره الاقتصادية؛ خاصة وأن استغلاله سيمنح الكثير من الدول فرصة التخلي أو التخفيض من الاعتماد على الغاز الطبيعي، لاسيما الولايات المتحدة الأمريكية والصين ودول الاتحاد الأوربي؛ كما سينعكس الأمر بشكل سلبي على الدول المنتجة للغاز الطبيعي بسبب التأثيرات الاقتصادية الناتجة عن التوسع في إنتاج ذلك البديل. أو بسبب آثاره البيئية الناتجة عن استخدامه كوقود الأحفوري، أو تقنية المستخدمة في استخراجه وإنتاجه وآثارها الضارة على الموارد المائية والأراضي. وسيتم تناول ذلك الموضوع من خلال السعي نحو تحديد الآثار الناتجة من التوسع في إنتاج الغاز غير التقليدي، وعما إذا كان استغلال الغاز غير التقليدي يعطي نتائج اقتصادية مرضية تبرر التكلفة التي سيتحملها المجتمع، والتساؤل وما الأثار التي يمكن أن يخلفها هذا النوع من مصادر الطاقة. من خلال خطة بحثية تتكون من مبحث تمهيدي بعنوان ماهية الغازات غير التقليدية، مبحث أول بعنوان دوافع التوسع في إنتاج الغازات غير التقليدية، مبحث الثاني بعنوان أهمية الغازات غير التقليدية والجدل حولها، مبحث الثالث بعنوان إنتاج الغازات غير التقليدية واستراتيجية الدول المتقدمة لأمن الطاقة، خاتمة، الاستنتاجات والتوصيات.
Energy is a key element in the process of economic development, and work to reduce its cost or support it leads to an expansion of the productive process and the prosperity of economic activity, and with the fluctuations in prices of fossil energy sources facing energy importing countries, there was an important lesson that should be taken advantage of, which is the need to diversify energy sources, And the pursuit of improving energy efficiency, and willingness to absorb a high degree of price volatility, and reduce the possibility of future shocks, in addition to the need for continued economic development by increasing the supply of energy that meets the demand for it as the engine of the economic process. The sudden advancement in the technology of unconventional gas production, especially in the United States, has aroused the interest of those interested in energy affairs, as this technical progress allowed greater economic contact with the supply of conventional natural gas, especially with the achievement of large-scale production of unconventional gas pools. In spite of what the technological developments of that industry promise to advance its place in unconventional gas, and the economic effects that it can have, especially with the development of discoveries of its resources over time, on both energy producers and importers. However, opinions were divided between opponents and supporters of its exploitation, whether due to its economic effects. Especially since its exploitation will give many countries the opportunity to give up or reduce dependence on natural gas, especially the United States of America, China and the countries of the European Union; The matter will also negatively affect the countries producing natural gas due to the economic impacts resulting from the expansion of production of that alternative. Or because of its environmental impacts resulting from its use as a fossil fuel, or the technology used in its extraction and production and its harmful effects on water resources and land. This issue will be addressed by seeking to determine the effects resulting from the expansion of unconventional gas production, and whether the exploitation of unconventional gas gives satisfactory economic results that justify the cost that will be borne by society, and the question and what effects this type of energy can have. Through a research plan consisting of an introductory topic entitled What are non-conventional gases, the first topic titled Motives for Expansion in the Production of Non-Conventional Gases, the Second Study entitled the Importance of Non- Conventional Gases and the Controversy Around them, the Third Study entitled “Non-conventional Gas Production and the Strategy of Advanced Countries for Energ Security, Conclusion, Conclusions and recommendations.
Keywords: الطاقة -- أمن الطاقة -- الغازات المصنعة -- الغاز غير التقليدي -- المشكلات البيئية